Cultivo de algodoeiro irrigado com efluente doméstico e adubação fosfatada - Gonçalo Filho, Francisco (2019)
The objective of this study was to evaluate the cultivation of herbaceous cotton fertirrigated with treated sewage effluent in a semi-arid environment. The research was developed in the experimental area of the Station of Wastewater Treatment and Reuse belonging to the Settlement Milagres, Apodi, Brazil, RN. The experiment was conducted in a randomized complete block design in subdivided plots, with 6 replicates. The cotton plants were fed with three different solutions containing treated domestic sewage (AR) and supply water (AA) (100% AA- control, 50% AA + 50% AR and 100% AR) with and without phosphate fertilization in pre-planting. The variables analyzed were the physical-chemical quality of the effluent, the nutrient contribution by the effluent, plant growth, gas exchange, mineral nutrition, phytomass and nutrient accumulation, fiber production and quality, and changes in soil physical properties. The analysis of the results indicated that the domestic sewage effluent used in the research is within the quality standards required for cotton irrigation and has a fertilizing effect on the crop, which had high leaf contents of N, K, Mg and Mn. The gaseous exchange (E, gs, A and Ci) per unit area of cotton leaf area decreased during the cycle and was lower when fertirrigation with treated domestic sewage water, however, it was superior when considering the whole plant, correctly reflecting the accumulation of assimilates. The percentage of fiber reduces proportionally to the increase of domestic effluent via fertigation, but does not compromise the productivity and quality of the cotton fiber produced. Pre-planting phosphorus fertilization did not influence the variables in the interaction with the presence and, or absence of effluent in the fertigation solution during the second cultural cycle due to the residual effect of the applied domestic effluent. The domestic effluent can be used as a source of nutrients for the cotton crop, as long as it is strictly monitored, especially the sodium (Na) contents and soil electrical conductivity (EC), to avoid soil degradation